Proceso de selección del personal de seguridad en el Gobierno Autónomo Descentralizado del Cantón Ventanas - Gonzalez Bajaña, Cristian Disney (2018)
The Personnel Selection and Recruitment process is defined as a procedure that seeks to find the worker that covers the appropriate position. The selection of personnel is of great importance to the company because it influences the strategic plans present and future of the organization. The process that is carried out in corresponding to the election of security personnel (municipal police), has a very exclusive quality at the moment of looking for those who are with the skills indicated to execute the position to be appointed, taking into consideration that it must different skills, knowledge and self-control in his personal life, which will allow the company to consider them more competitive